Semantic Analysis of Similes in The Weeknd’s Selected Song Lyrics - I Gede Mardika Pujana; Sang Ayu Isnu Maharani; Ni Made Ayu Widiastuti (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2026)
This research examines the role of figurative language, particularly similes, in expressing abstract emotions through vivid imagery in The Weeknd’s selected songs. The study aims to identify explicit similes marked by like and as and analyze how their connotative meanings reflect disappointment, heartbreak, and falling in love. A qualitative descriptive method was employed, using the lyrics of Adaptation, King of the Fall, and Nothing Compares as the main data. The data were collected through documentation and analyzed through identification, classification, interpretation, and explanation based on Leech’s theory of meaning. The results identified nine similes across the three songs. Two similes in Adaptation reflect disappointment and self-regret, particularly concerning the singer’s inability to maintain a pure and sincere relationship. Five similes in King of the Fall express heartbreak through emotional burden, exhaustion, despair, and relational emptiness. Meanwhile, two similes in Nothing Compares represent falling in love through emotional attachment, admiration, and the uniqueness of romantic connection. These findings demonstrate that similes function not merely as decorative literary devices but as important semantic tools that transform abstract emotional experiences into concrete and meaningful imagery, strengthening emotional expression and enabling listeners to better understand the themes conveyed in contemporary song lyrics.